Somatic embryos response against iron stress in in-vitro culture condition of East Kalimantan (Indonesia) rice - NURHASANAH NURHASANAH; RAMITA; BAMBANG SUPRIYANTO; WIDI SUNARYO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nurhasanah, Ramita, Supriyanto B, Sunaryo W. 2019. Somatic embryos response against iron stress in in-vitro culture condition of East Kalimantan (Indonesia) rice. Biodiversitas 20: 2288-2294. Iron toxicity is major abiotic stress that limits rice production in most tropical regions. A high iron concentration will lead to the abnormal growth and development, decreased yield, and even death of the plant. Compared to other recommended treatments to overcome iron toxicity problems, the use of tolerant cultivars is considered the most effective and efficient approach. In this study, the tolerant character against iron stress was developed using East Kalimantan local rice cultivars through somaclonal variation and in vitro selection. The somatic embryos from four indica rice cultivars, Mayas Pancing, Gedagai, Siam, and Serai, were selected in iron-containing media. Five levels of iron concentrations were applied in the selection media 0; 27.8; 55.6; 83.4, and 111.2 mg.L-1 of FeSO4.7H2O. The media acidity was adjusted to pH 4.00 for iron-containing media and 5.8 for the zero iron concentration (without iron). The results showed that the survival ability of embryonic calli (EC) was significantly influenced by the level of iron concentration. The absence of an iron source in the selection media led to lower EC survival. The percentage of EC survival ability was even lower than that of the presence of two folds of normal iron concentration (55.6 mgL-1 of FeSO4.7H2O). Three and four folds of the normal iron concentration (83.6 mg.L-1 and 111.2 mg.L-1 FeSO4.7H2O) mostly produced the lowest percentage of EC survival for the four local rice cultivars. Mayas Pancing had better tolerance to iron stress and the highest EC survival number compared to other genotypes. The role of genotype was clearly observed in the regeneration ability of EC. Plantlets were only produced on the EC from the Serai Gunung and Siam cultivars.